Pelatihan Pengolahan Data Menggunakan Minitab Bagi Pegawai Fungsional Perencana - Dara Puspita Anggraeni; Ria Maulina; Irma Risvana Dewi; Rio Satriyantara; Alfian Eka Utama (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
The purpose of this community service is to test the effectiveness of the data processing workshop using minitab for functional planning officers.This workshop was held on April 14, 2022 at BAPPEDA KLU. This workshop was attended by 10 participants. The workshop method is lecturing statistical material and data processing practice using minitab. As for comparing the average pre-test and post-test scores of participants, the Wilcoxon Match Pairs Test method was used. The test results show z count = 21.00, while it is known that the value of z table = z (1-0.05) = 1.64. z count > z table, it means that the average post-test score is significantly higher than the average pre-test score or in other words, community service in the form of training has an effect on the data processing capabilities of planning functional employees at BAPPEDA KLU